Bukti Empiris Pengaruh Spesialisasi Industri Auditor terhadap Earnings Response Coefficient - Sekar Mayangsari (The Indonesian Journal of Accounting Research, 2013)
This study investigates the effect of auditor industry specialization on the earnings response coefficients (ERC). Prior work (DeAngelo 1981)  has suggested that auditors offer different levels of audit quality. One component of the quality difference across auditors is industry specialization (Craswell et al. 1995 and Hogan and Jeter 1999). Teoh dan Wong (1993) argue that audit quality is positively associated with the client’s quality of earnings and the earnings response coefficient (ERC), which is the responsiveness of the stock market to information about unexpected earnings. This study uses the sample of unregulated companies during1996-2000. The results suggest that, after controlling another variables that correlates with ERC, clients of industry specialist auditor have higher ERCs than clients of non-specialist auditors. Interestingly, there is no difference response statistically significance between firms that were audited by specialist auditor and by nonspecialist auditor.